Evaluating symptoms of chronic rhino sinusitis and most common sinuses affected - Qays Jaafar Khalaf (Diyala Journal of Medicine, 2023)
Background: Chronic rhinosinusitis is a common condition that significantly affect the quality of life, high health-care consumption and significant comorbidity.